Genome-wide screening and functional analysis of protein glycosylation-related genes involved in tomato fruit ripening - Bowen Li; Ye Liu; Peiwen Wu; Zheng Bian; Cailian Wang; Chunyang Wang; Na Ren; Yangyang Han; Benzhong Zhu (Plant Science, 2026)

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Regulation of mycelium–egg white protein composite formation by pH and ionic strength - Mukadaisi Muhedaner; Ziqing Song; Na Huang; Mengjun Li; Guanghong Zhou; Keping Ye (Food Bioscience, 2026)

High-pressure CO₂ spraying of electret melt-blown polypropylene for piezoelectric self-sensing respiratory monitoring masks - Jiahui Xu; Xiaoyue Zou; Ning Cao; Yunchen Yao; Yuxin Jia; Na Zheng; Zhenshu Chen; Youqiang Yang; Zhanquan Lu; Xiangrong Chen; Pengfei Xie; Cheng Li; et al. (Chemical Engineering Journal, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Study on the Effects of Feeding and Starvation on the External Morphology and Gonadal Development of Artificially Matured American Eel - Lan Wang; Jialun Liu; Zhongmei Yang; Tongxi Ai; Feng Zhao; Keji Jiang; Lei Gao; Mingfei Li; Ye Ding; Na Zhao; Wei Jiang; Xinhui Wei; et al. (Fishes, 2026)
The aim of this study is to investigate how external nutrient supply affects the allocation of reproductive energy during artificial ripening of American eels (Anguilla rostrata), as well as the physiological regulatory mechanisms involved in their bodies. Healthy female American eels were selected for the experiment and randomly divided into two groups: feeding group and starvation group (simulating the natural migration of American eels without eating). The initial weight of the feeding group was (308.43 ± 36.99 g), and the initial weight of the starvation group was (291.67 ± 63.31 g). The entire experiment was divided into two stages: the first stage was a 6-month nutritional reinforcement period, during which the feeding group was regularly fed with Vannamei shrimp, while the starvation group was not fed throughout the entire process. The second stage was a 3-month artificial ripening stage, during which both groups of eels stopped feeding. Inject 1 mL of mixed hormone (containing 6.5 mg of carp pituitary extract CPE+200 IU human chorionic gonadotropin HCG per mL per week) into each eel for a total of 12 injections to induce gonadal maturation. Both groups of eels did not die during the experiment, with a survival rate of 100%. As the gonads continue to develop and mature, the growth and development advantages of the feeding group of eels are very obvious: body weight, chest circumference, and gonadal index are significantly higher than those of the starvation group. After completing 12 hormone injections, the gonadal index of the feeding group reached (32.72 ± 7.01%), while that of the starvation group was only (4.35 ± 2.48%). Under artificial ripening conditions, the egg diameter of the feeding-eel group increased rapidly in the later stage of the experiment. The growth rate of eggs in the starvation group was slow, and the final egg diameter was significantly smaller. The diameters of the nuclei of both groups of oocytes increased synchronously with the progress of the experiment; the number of nucleoli in the feeding group first increased and then decreased, while the number of nucleoli in the starvation group continued to increase. The oil droplets inside both sets of eggs gradually increased in size, and the oil droplets fed to the eggs in the middle and late stages of maturation had a larger volume. Hormone test results showed that the testosterone (T) level in the eel fed group increased significantly in the later stage of the experiment. This indicates that adequate nutrition can alleviate the inhibition of the reproductive endocrine axis through positive feedback regulation of the pituitary gonad (BPG) axis. Nutritional reinforcement before ripening can promote gonadal development and enhance reproductive capacity by regulating the distribution of nutrients between muscles and gonads. The results of this study provide a solid theoretical basis for improving the nutritional management plan for parent fish in the fully artificial breeding process of American eels.

Therapeutic effects of fucoidan with different molecular weight on atopic dermatitis - Zhiyan Wang; Yanbin Lai; Qing Li; Na Zhang; Bingde Zheng; Hongjie Yang; Yayan Huang; Yucheng Yang; Xueqin Zhang; Jing Ye; Meitian Xiao (Food Bioscience, 2026)

Effects of Pediococcus pentosaceus and tea polyphenols on biogenic amines, volatile compounds, and microbial Community in Fermented Sausage - Erke Sun; Xueying Sun; Weiqi Qin; Shiqi Hao; Yanrong Chen; Lina Sun; Ye Jin; Na Wang; Rugang Tian; Hui Li; Jie Kang; Xun Xiao; et al. (Food Chemistry, 2026)

Enhanced metal-organic framework-driven deep learning-assisted magnetic crystal paper aptsensor for two-step sensitization and in-situ detection of pathogenic bacteria - Lulu Cao; Yuwei Ren; Shengshi Jiang; Hui Li; Maoling Hu; Xin Zhang; Xiaoyu Yu; Weichao Wu; Mengyu Li; Zhao Liang; Na Ling; Hongzhou Chen; et al. (Chemical Engineering Journal, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Insight the active sites and adsorption-desorption mechanism on red mud adsorbent for direct air capture of CO2 with excellent cycling performance - Na Gao; Jin Zhang; Ziyan chen; Bin Li; Mingli Fu; Daiqi Ye (Chemical Engineering Journal, 2026)

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

Millennial- to centennial-scale record of organic carbon accumulation and its periodic occurrence in the Yellow Sea since the last deglaciation - Yuying Zhang; Limin Hu; Yazhi Bai; Lina Jin; Hyung Jeek Kim; Na Li; Song Zhao; Jun Ye; Yonghua Wu; Xiao Wu; Xiting Liu; Xun Gong; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

NADH-driven bioreductive degradation of azo dyes: Mechanisms of high NADH production, electron transfer, and microbial responses - Yiting Qin; Xuehui Xie; Dongyang Li; Ziyi Wu; Jiajie Liu; Wanting Li; Daijie Tang; Songwei Chen; Yiwen Zhang; Na Liu; Qingyun Zhang; Ye Chen (Journal of Hazardous Materials, 2026)

D-allulose alleviates DSS-induced colitis via regulating gut microbiota and bile acid metabolism - Gaoqi Ye; Na Xi; Genying Li; Ziyuan Wang; Zhaofeng Li; Tongcheng Xu; Fangling Du; Guangpeng Dou; Yiman Zhang; Jie Liu (Food Research International, 2026)

Liquid-derived carbon encapsulated nanoporous SiOx anode for long-cycle lithium-ion batteries - Liewu Li; Chufang Chen; Qianqian Jiang; Zhencheng Huang; Jie Peng; Haoran Wei; Xiaoyu Gong; Na Feng; Shenghua Ye; Xuming Yang; Xiangzhong Ren; Jianhong Liu; et al. (Chemical Engineering Journal, 2026)

One-time nitrogen application increased soil and canopy ammonia emissions in maize fields - Kedi Zhang; Yang Yang; Xiaoyu Ni; Qing Ma; Ye Yang; Ronghao Cai; Na Li (Atmospheric Pollution Research, 2026)

Enhancing soil ammonium retention with humic acid-modified bentonite - Na Li; Sinan Li; Feng Li; Xiaohua Shen; Xiaoyu Ni; Ye Yang; Yang Yang (Journal of Soils and Sediments, 2026)

Novel interface-enhanced bimetallic nanozyme-mediated magnetic integrated nanoplatform for integrated prevention and control of pathogenic bacteria - Xiaoyu Yu; Xin Zhang; Yuwei Ren; Rui Jiao; Hui Li; Mengyu Li; Weichao Wu; Na Ling; Danfeng Zhang; Jianghua Cheng; Yingwang Ye (Analytica Chimica Acta, 2026)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

Effect of ammonium chloride on the salt-induced cohesive behavior of egg yolk liquid and its plasma with granules - Yufei Ye; Hang Li; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Chemistry, 2025)

Involvement of ductal reaction in Di-(2-ethylhexyl)-phthalate-caused hepatic fibrosis: Molecular mechanisms and potential intervention strategies - Xinru Du; Shu Zhang; Sha Liu; Yancheng Gao; Zhendong Wang; Na Dong; Sisi Song; Qinming Hui; Ziyi Wang; Yue Ma; Chunxiao Zhou; Ye Yang; et al. (Chemico-Biological Interactions, 2025)

Corrigendum to “Uncovering key genes of K1 capsule Cronobacter on environmental resilience” [Food Bioscience 67 (2025) 106224] - Zongyang Li; Na Ling; Shengshi Jiang; Xihao Wang; Yingwang Ye (Food Bioscience, 2025)

Novel application of L-type phenyllactate in the “three birds one stone” control of Burkholderia gladioli growth and bongkrekic acid production in Auricularia auricula - Rui Jiao; Hui Li; Xiyan Zhang; Yuwei Ren; Na Ling; Yingwang Ye (Food Microbiology, 2025)

Enhancing capacitive deionization with element-doped carbon nanotube electrodes for selective uranium ion removal - Na Liu; Xinhua Huang; Yulin Ye; Hui Li; Ruikun Zhao; Guangzhi Hu (Desalination, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Vertical distribution and regional transport of air pollution over Northeast China: Insights from an intensive aircraft study - Ye Shan; Yujiao Zhu; Haoxin Sui; Na Zhao; Hongyong Li; Liang Wen; Tianshu Chen; Yanbin Qi; Wenlong Qi; Xinfeng Wang; Yuqiang Zhang; Likun Xue; et al. (Atmospheric Environment, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

(±)-Laevigiol A, a pair of new enantiomeric phenylpropanoids from the leaves and twigs of Croton laevigatus Vahl. and their anti-Alzheimer’s disease activities - Yu-Bin Lu; Mi-Na Yang; Hui-Jie Li; Li-Jia Ye; Le-Le Guo; Miao Zhang; Chun-Min Liu; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Phytochemistry Letters, 2025)

Mechanism of fatty acid synthesis metabolism during tuber swelling period of Chinese yam - Na Li; Yanfang Zhang; Xiuwen Huo; Shuchun Guo; Ningning Suo; Ye Tang (Food Chemistry, 2025)

Fate of myofibrillar protein-bound Nε-(carboxymethyl)lysine in the presence of the human colonic microbiota after gastrointestinal digestion - Shuqi Hao; Zeyu Lu; Mengyu Ye; Na Li; Jiayi Hu; Wei Quan; Jiwen Cheng; Huaide Xu; Mei Li (Food Bioscience, 2025)

Bimetallic organic framework-derived multifunctional signal marker-driven ultra-magnetic nanoplatform for sensitive detection and efficient sterilization of methicillin-resistant Staphylococcus aureus - Xin Zhang; Xiaoyu Yu; Yuwei Ren; Rui Jiao; Hui Li; Xiyan Zhang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; Yingwang Ye (Chemical Engineering Journal, 2025)

Adsorbent application and nitrogen deep placement reduced ammonia emissions in wheat fields - Yang Yang; Weizheng Shu; Ye Yang; Xiaoyu Ni; Yuejin Wu; Wenge Wu; Na Li (Soil and Tillage Research, 2025)

Prevalence of hypervirulent Klebsiella pneumoniae and application of the novel Klebsiella phage vB_KpnP_D39 for biocontrol of serotypes K1, K2, and K57 in prepared food-related samples - Diwei Zhang; Rui Jiao; Bin Cheng; Xiyan Zhang; Hanfang Chen; Hui Li; Xiangyu Cheng; Na Ling; Yingwang Ye (International Journal of Food Microbiology, 2025)

Uncovering key genes of K1 capsule Cronobacter on environmental resilience - Zongyang Li; Na Ling; Shengshi Jiang; Xihao Wang; Yingwang Ye (Food Bioscience, 2025)

Recent advances and future prospects of wearable sensors based on nanomaterial sensing mechanisms for biosafety monitoring - Xiaoyu Yu; Hui Li; Junwen Wang; Xin Zhang; Rui Jiao; Yuwei Ren; Danfeng Zhang; Na Ling; Yingwang Ye (Chemical Engineering Journal, 2025)

Metabolic engineering of Halomonas for effective production of tryptophan-derived compounds - Kai-Xuan Liu; Wei Chen; Yage Xiao; Ye Zheng; Xinying Xie; Weilin Li; Huaiming Wang; Hui Wang; Yi-Na Lin; Jian-Wen Ye (Chemical Engineering Journal, 2025)

Green synthesis of polysaccharide-based Ag@AgCl photoactive porous hydrogel spheres for enhanced visible light photocatalytic degradation of organic pollutants - Yutong Wen; Na Qi; Ye Zhang; Zhiqi Li; Bing Fan; Meng Zhang; Ying Li (Carbohydrate Polymers, 2025)

Overexpression of the Wbl family regulator whiDsbh modulates secondary metabolite biosynthesis in Streptomyces - Xuedong Zhang; Jiabin Wang; Haoran Shi; Na Zhou; Shanshan Li; Lan Ye; Wensheng Xiang; Xiangjing Wang; Yanyan Zhang (World Journal of Microbiology and Biotechnology, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

Correlation between the physicochemical and bacteriological qualities of pickled chili pepper (Paojiao) and its nitrite degradation study - Jianhui Wang; Miao Liu; Linlin Ye; Xiaoyi Hou; Zhenyu Li; Linzhi Tang; Na Deng; Hui Li (Food Bioscience, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Review on recent advancements in understanding acetylsalicylic acid-induced gastrointestinal injury: mechanisms, medication, and dosage refinement - Jiahui Zhou; Na Li; Xinzhong Li; Jingxue Ye; Min Wang; Guibo Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Amino-tuned S-scheme ZIF nano-heterojunction coating up/downconversion nanoparticles for near-infrared-triggered catalytic therapy and bioimaging - Chunsheng Li; Jiawei Qu; Yunlong Li; Shuang Liu; Zhengyang Tang; Qiang Wang; Jin Ye; Jiating Xu; Na Niu; Ligang Chen; Piaoping Yang (Chemical Engineering Journal, 2025)

Synergistic effects of acid-plasma treatment on CO2 capture towards carbon materials - Zhiping Ye; Chuang Han; Meilan Pan; Liang Zhao; Na Liu; Anton Nikiforov; Karen Leus; Nathalie De Geyter; Rino Morent; Jun Chen; Junhua Li (Chemical Engineering Journal, 2025)

Platinum-based fluorescent nanozyme-driven “loong frolic pearls” multifunctional nanoplatform for tri-mode ultrasensitive detection and synergistic sterilization of Burkholderia gladioli - Rui Jiao; Yuwei Ren; Xiyan Zhang; Hui Li; Ying Zhan; Xin Zhang; Xiaoyu Yu; Na Ling; Yingwang Ye (Food Chemistry, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

Polystyrene nanoplastics induce apoptosis, histopathological damage, and glutathione metabolism disorder in the intestine of juvenile East Asian river prawns (Macrobrachium nipponense) - Yiming Li; Yucong Ye; Xiaoyi Zhu; Siwen Li; Na Rihan; Zongli Yao; Zhen Sun; Pengcheng Gao; Yunlong Zhao; Qifang Lai (Science of The Total Environment, 2024)

Study on the influence of combined utilization of air-fog curtain on fully mechanized face - Na Qin; Haiming Yu; Yuxi Ye; Yao Xie; Xu Li (Process Safety and Environmental Protection, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

Calcium chloride seed priming: A dual-action strategy for enhancing Cyrtorhinus lividipennis attraction and deterring brown planthopper infestations in rice - Zhong-Yan Zhu; Xiao-Bao Wu; Jia-jia An; Qian-Qian Deng; Jun Wang; Li-Na Chen; Mao Ye (Crop Protection, 2024)

Boosting solvent resistance and structure stability of degradable polyester through extended-chain crystal structure: A preliminary case of oil/water separation membrane - Jia-Yao Chen; Na Li; Siyang Wang; Tian-Yu Wu; Xiaoyu Meng; Hai-Mu Ye (Journal of Environmental Chemical Engineering, 2024)

Probiotic Potential, Antibacterial, and Antioxidant Capacity of Aspergillus luchuensis YZ-1 Isolated From Liubao Tea - Xiyan Zhang; Rui Jiao; Hui Li; Dexin Ou; Danfeng Zhang; Yizhong Shen; Na Ling; Yingwang Ye (Probiotics and Antimicrobial Proteins, 2024)

Dynamic pathology and pathogen distribution of the yeast Metschnikowia bicuspidata in the Chinese mitten crab ( Eriocheir sinensis ) - Xinran Shi; Na Sun; Jiannan Liu; Senting Pu; Zhouling Chen; Dong Sheng; Kexin Hao; Xiaodong Li; Shigen Ye (Journal of Fish Diseases, 2024)
In this study, the “milky disease” model of Eriocheir sinhensis was constructed via intramuscular injection with the pathogenic yeast Metschnikowia bicuspidata . The dynamic pathological changes of E. sinensis after injection were elucidated with two staining methods (haemotoxylin‐eosin and alcian blue periodic acid‐Schiff) and fluorescence in situ hybridization technology. Anatomical observation revealed three stages of the “milky disease”: no clinical signs (1–4 days after infection), the appearance of signs of disease (5–7 days), and significant liquefaction (10 days). Histological observation also revealed three stages of the disease: yeast diffusion (1–2 days after infection), yeast slow development (3–4 days), and yeast rapid proliferation (5 days). And FISH technique was suitable for the early detection of infection with M. bicuspidata in E. sinensis . We found that M. bicuspidata spread to the whole body of the crab through the haemolymph and developed into fungal septicaemia. These results elucidate the systemic pathological characteristics of “milky disease” in E. sinensis and suggest the pathogenic mechanism of M. bicuspidata .

Estimation of ammonia emissions from rice fields under different N inputs in China - Na Li; Xiaoyu Ni; Ye Yang; Yuejin Wu; Weizheng Shu; Wenge Wu; Yang Yang (Resources, Conservation and Recycling, 2024)

Triple modal aptasensor arrays driven by CHA-mediated DNAzyme for signal-amplified atrazine pesticide accumulation monitoring in agricultural crops - Jintong Liu; Na Li; Linyao Ye; Lin Zhou; Guanghao Chen; Jie Tang; Heng Zhang; Hong Yang (Journal of Hazardous Materials, 2024)

Adsorptive removal of aflatoxin B1 via spore protein from Aspergillus luchuensis YZ-1 - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Journal of Hazardous Materials, 2024)

Comparison of intestinal absorption of soybean protein isolate-, glutenin- and peanut protein isolate-bound Nε-(carboxymethyl) lysine after in vitro gastrointestinal digestion - Shuqi Hao; Mengyu Ye; Na Li; Zeyu Lu; Wei Quan; Huaide Xu; Mei Li (Food Research International, 2024)

Transformation of mulberry polyphenols by Lactobacillus plantarum SC-5: Increasing phenolic acids and enhancement of anti-aging effect - Mengyao Li; Xiangxiu Xu; Yifan Jia; Yuan Yuan; Guo Na; Ling Zhu; Xiaowei Xiao; Yamin Zhang; Haiqing Ye (Food Research International, 2024)

Dietary lipid supplementation alleviated the impacts of polystyrene nanoplastic exposure in Litopenaeus vannamei - Yiming Li; Yucong Ye; Haojuan Yuan; Siwen Li; Na Rihan; Xingguo Liu; Yunlong Zhao; Xuan Che (Aquatic Toxicology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Transcriptomic and biochemical analyses reveal the antifungal mechanism of cell-free supernatant from Aspergillus luchuensis YZ-1 against Aspergillus flavus - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Food Bioscience, 2024)

High-performance antibacterial tight ultrafiltration membrane constructed by co-deposition of dopamine and tobramycin for sustainable high-salinity textile wastewater management - Wenyuan Ye; Fan Yu; Zijian Yu; Na Kong; Xiaoyan Lin; Riri Liu; Jiale Du; Xuan Huang; Ailiang Gu; Sotto Arcadio; Wenyi Zhang; Xuewei Li; et al. (Desalination, 2024)

A small landslide induced a large disaster prior to the heavy rainy season in Jinkouhe, Sichuan, China: characteristics, mechanism, and lessons - Runing Hou; Zhi Li; Weihao Ye; Taixin Peng; Shufeng Tian; Ningsheng Chen; Na Huang; Marcelo Somos-Valenzuela (Landslides, 2024)

High starch and hemicellulose labile C degradation functional genes increase soil CO2 emissions follow straw return - Jin Li; Jiaqi Li; Xuhong Ye; Bol Roland; Xinxin Jin; Yanyu Han; Na Yu; Hongtao Zou (Applied Soil Ecology, 2024)

Biotransformation of HBCDs by the microbial communities enriched from mangrove sediments - Fei Yu; Bing Zhang; Yongjin Liu; Wenqi Luo; Haonan Chen; Jun’na Gao; Xueying Ye; Jin Li; Qingyi Xie; Tao Peng; Hui Wang; Tongwang Huang; et al. (Journal of Hazardous Materials, 2024)

Spatiotemporal characteristics of water exchange between the Andaman Sea and the Bay of Bengal - Yihao Wang; Feng Zhou; Xueming Zhu; Ruijie Ye; Yingyu Peng; Zhentao Hu; Haoran Tian; Na Li (Acta Oceanologica Sinica, 2024)

Long-term organic amendments increase the vulnerability of microbial respiration to environmental changes: Evidence from field and laboratory studies - Chenglong Ye; Na Li; Juan Gui; Mengyi Zhu; Yan Zhou; Daming Li; Kuihu Jiao; Bryan S. Griffiths; Shuijin Hu; Manqiang Liu (Science of The Total Environment, 2024)

Exposure to polystyrene nanoplastics induces apoptosis, autophagy, histopathological damage, and intestinal microbiota dysbiosis of the Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Haojuan Yuan; Na Rihan; Mingming Han; Xingguo Liu; Tian Zhu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Facile construction of superhydrophobic/superoleophilic melamine sponges with durability and antifouling for selective oil absorption and effective oil/water separation - Ye Li; Xin Li; Le Xu; Yihang Yang; Zhaojian Gao; Yingmei Zhou; Na Zhang; Hongri Wan; Teng Chen (Journal of Environmental Chemical Engineering, 2024)

Characterization of the broad-spectrum phage vB_CsaM_CBT2 and its inhibition of multidrug-resistant Cronobacter sakazakii in powered infant formula - Bin Cheng; Diwei Zhang; Ting Wang; Hanfang Chen; Yuhang Wang; Yang Wang; Zongyang Li; Na Ling; Yingwang Ye (Food Control, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Clinically relevant stratification of lung squamous carcinoma patients based on ubiquitinated proteasome genes for 3P medical approach - Jingru Yang; Serge Yannick Ouedraogo; Jingjing Wang; Zhijun Li; Xiaoxia Feng; Zhen Ye; Shu Zheng; Na Li; Xianquan Zhan (EPMA Journal, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Polystyrene nanoplastics exposure alters muscle amino acid composition and nutritional quality of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Degradation of n-hexane by the high-throughput double dielectric barrier discharge: Influencing factors, degradation mechanism and pathways - Ke Li; Ning Jiang; Xiuwen Zhang; Kai Chen; Na Liu; Anton Nikiforov; Jun Chen; Zhiping Ye (Journal of Environmental Chemical Engineering, 2024)

Synthesis of multiwalled carbon nanotubes/metal-organic framework composite for the determination of neonicotinoid pesticides in medicine and food homology products - Haizhi Huang; Na Li; Ya Chen; Xuping Shentu; Xiaoping Yu; Zihong Ye (Food Chemistry, 2024)

Polystyrene nanoplastics induce lipid metabolism disorder and alter fatty acid composition in the hepatopancreas of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Effect of ferric ions on Cronobacter sakazakii growth, biofilm formation, and swarming motility - Yang Wang; Na Ling; Yaping Wang; Dexin Ou; Zhao Liang; Guoqing Li; Hongyuan Zhao; Yingwang Ye (International Journal of Food Microbiology, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

Nitroproteomics is instrumental for stratification and targeted treatments of astrocytoma patients: expert recommendations for advanced 3PM approach with improved individual outcomes - Wenshuang Jia; Xiaoxia Gong; Zhen Ye; Na Li; Xianquan Zhan (EPMA Journal, 2023)

LuxS-deficiency reduces persistence of Cronobacter to low-moisture but contributes to virulence after rehydration - Na Ling; Zongyang Li; Yuhang Wang; Qingping Wu; Yingwang Ye; Jumei Zhang (Food Research International, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Transcriptomic analysis reveals novel desiccation tolerance mechanism of Cronobacter based on type VI secretion system inhibition - Yang Wang; Na Ling; Rui Jiao; Xiyan Zhang; Yuwei Ren; Hui Li; Wenhua Zhao; Qingping Wu; Yingwang Ye (Food Research International, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Polystyrene nanoplastics decrease nutrient accumulation, disturb sex hormones, and inhibit reproductive development in juvenile Macrobrachium nipponense - Yiming Li; Yucong Ye; Na Rihan; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Scutellarin Acts via MAPKs Pathway to Promote M2 Polarization of Microglial Cells - Hao-Lun Chen; Li Yang; Xiao-Li-Na Zhang; Qiu-Ye Jia; Zhao-Da Duan; Juan-juan Li; Li-yang Zheng; Teng-teng Liu; Zhi Qi; Yun Yuan; Chun-Yun Wu (Molecular Neurobiology, 2023)

Role and Mechanism of BMP4 in Regenerative Medicine and Tissue Engineering - Yiqi Pan; Zhiwei Jiang; Yuer Ye; Danji Zhu; Na Li; Guoli Yang; Ying Wang (Annals of Biomedical Engineering, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Modeling Secondary Organic Aerosols in China: State of the Art and Perspectives - Jingyi Li; Haowen Zhang; Lin Li; Fei Ye; Hongli Wang; Song Guo; Na Zhang; Momei Qin; Jianlin Hu (Current Pollution Reports, 2023)

Refined-JinQi-JiangTang tablet ameliorates hypertension through activation of FGF21/FGFR1 axis in fructose-fed rats - Siming Li; Xiaoling Li; Jing Fan; Xinhang Jia; Hemeng Wang; Fangxin Dong; Haoyang Mao; Chen Zhang; Wenfei Wang; Ye Jiang; Lijun Yan; Na Zhang (Journal of Natural Medicines, 2022)

Two new N -acetyl-ᴅ-glucosamine derivatives from the medical algae-derived endophytic fungus Penicillium chrysogenum - Jing Chen; Li-Na Huo; Yuan Gao; Yun-Li Zhang; Ye Chen (Natural Product Research, 2022)

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

Discovery of N-phenyl-1-(phenylsulfonamido)cyclopropane-1-carboxamide analogs as NLRP3 inflammasome inhibitors - Wanwan Li; Zhongqiang Cao; Junjie Cheng; Feiyu Chen; Shuai Li; Yiwei Huang; Long Tai Zheng; Na Ye (Medicinal Chemistry Research, 2021)

Maize Straw Deep-Burying Promotes Soil Bacteria Community Abundance and Improves Soil Fertility - Jiaqi Li; Xuhong Ye; Yuling Zhang; Ji Chen; Na Yu; Hongtao Zou (Journal of Soil Science and Plant Nutrition, 2021)

Geospatial and Semantic Mapping Platform for Massive COVID-19 Scientific Publication Search - Xinyue Ye; Jiaxin Du; Xi Gong; Saiyang Na; Weimin Li; Sonali Kudva (Journal of Geovisualization and Spatial Analysis, 2021)

Design and Synthesis of Polymer Prodrugs for Improving Water-Solubility, Pharmacokinetic Behavior and Antitumor Efficacy of TXA9 - Yiwen Li; Chun Ye; Chengcheng Cai; Meng Zhao; Na Han; Zhihui Liu; Jianxiu Zhai; Jun Yin (Pharmaceutical Research, 2020)

Emerging role of semaphorin-3A in autoimmune diseases - Li-Na Liu; Xiao-Mei Li; Dong-Qing Ye; Hai-Feng Pan (Inflammopharmacology, 2018)

Early diagnosis of acute kidney injury in aged patients undergoing percutaneous coronary intervention - Hong-hua Ye; Gen Shen; Qun Luo; Fang-fang Zhou; Xiao-ling Xie; Chun-yan Wang; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2018)

Immunization with an adenovirus-vectored TB vaccine containing Ag85A-Mtb32 effectively alleviates allergic asthma - Yiling Zhang; Ying Feng; Liang Li; Xianmiao Ye; Jinlin Wang; Qian Wang; Pingchao Li; Na Li; Xuehua Zheng; Xiang Gao; Chufang Li; Feng Li; et al. (Journal of Molecular Medicine, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

A novel Enterovirus 96 circulating in China causes hand, foot, and mouth disease - Yi Xu; Yisuo Sun; Jinmin Ma; Shuru Zhou; Wei Fang; Jiawei Ye; Limei Tan; Jingkai Ji; Dan Luo; Liqiang Li; Jiandong Li; Chunxiao Fang; et al. (Virus Genes, 2017)

Generation of obese rat model by transcription activator-like effector nucleases targeting the leptin receptor gene - Yuting Chen; Wenqing Lu; Na Gao; Yi Long; Yanjiao Shao; Meizhen Liu; Huaqing Chen; Shixin Ye; Xueyun Ma; Mingyao Liu; Dali Li (Science China Life Sciences, 2017)
The laboratory rat is a valuable mammalian model organism for basic research and drug discovery. Here we demonstrate an efficient methodology by applying transcription activator-like effector nucleases (TALENs) technology to generate Leptin receptor ( Lepr ) knockout rats on the Sprague Dawley (SD) genetic background. Through direct injection of in vitro transcribed mRNA of TALEN pairs into SD rat zygotes, somatic mutations were induced in two of three resulting pups. One of the founders carrying bi-allelic mutation exhibited early onset of obesity and infertility. The other founder carried a chimeric mutation which was efficiently transmitted to the progenies. Through phenotyping of the resulting three lines of rats bearing distinct mutations in the Lepr locus, we found that the strains with a frame-shifted or premature stop codon mutation led to obesity and metabolic disorders. However, no obvious defect was observed in a strain with an in-frame 57 bp deletion in the extracellular domain of Lepr . This suggests the deleted amino acids do not significantly affect Lepr structure and function. This is the first report of generating the Lepr mutant obese rat model in SD strain through a reverse genetic approach. This suggests that TALEN is an efficient and powerful gene editing technology for the generation of disease models.

Enhancement of Cd phytoextraction by hyperaccumulator Sedum alfredii using electrical field and organic amendments - Wendan Xiao; Dan Li; Xuezhu Ye; Haizhou Xu; Guihua Yao; Jingwen Wang; Qi Zhang; Jing Hu; Na Gao (Environmental Science and Pollution Research, 2017)

Identification of russet-associated microRNAs in the exocarp of a Dangshansuli pear mutant (Pyrus bretschneideri Rehd.) by high-throughput sequencing - Wei Heng; Bing Jia; Hai-na Huang; Jin-yu Yang; Zi-teng Wang; Pu Liu; Li Liu; Zhen-feng Ye; Li-wu Zhu (Tree Genetics & Genomes, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

In vivo activity of vancomycin combined with colistin against multidrug-resistant strains of Acinetobacter baumannii in a Galleria mellonella model - Haifei Yang; Na Lv; Lifen Hu; Yanyan Liu; Jun Cheng; Ying Ye; Jiabin Li (Infectious Diseases, 2016)

cDNA cloning, expression, and immunolocalization of gonad-inhibiting hormone (GIH) in Litopenaeus vannamei - Guang-li Li; Si-ping Deng; Shu-na Jiang; Man Ye; Hua-pu Chen; Siuming F. Chan; Chun-hua Zhu (Genes & Genomics, 2015)

Effects of different cleaning treatments on heavy metal removal of Panax notoginseng (Burk) F. H. Chen - Liu Dahui; Xu Na; Wang Li; Cui Xiuming; Guo Lanping; Zhang Zhihui; Wang Jiajin; Yang Ye (Food Additives & Contaminants: Part A, 2014)

Assessment of antioxidant defense system responses in the hepatopancreas of the freshwater crab Sinopotamon henanense exposed to lead - Na Liu; Lan Wang; Bo Yan; Yongquan Li; Fei Ye; Jing Li; Qian Wang (Hydrobiologia, 2014)

Essential oil from Zanthoxylum bungeanum Maxim. and its main components used as transdermal penetration enhancers: a comparative study - Yi Lan; Hui Li; Yan-yan Chen; Ye-wen Zhang; Na Liu; Qing Zhang; Qing Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Simultaneous determination by UPLC-MS/MS of seven bioactive compounds in rat plasma after oral administration of Ginkgo biloba tablets: application to a pharmacokinetic study - Wen-ping Wang; Na Liu; Qian Kang; Pei-pei Du; Yi Lan; Bo-chen Zhao; Yan-yan Chen; Qing Zhang; Hui Li; Ye-wen Zhang; Qing Wu (Journal of Zhejiang University-SCIENCE B, 2014)

HER-2 overexpression and survival in colorectal cancer: a meta-analysis - Chao Li; Da-ren Liu; Long-yun Ye; Ling-na Huang; Sanjay Jaiswal; Xiao-wen Li; Hou-hong Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Haemocyte Apoptosis of the Tiger Shrimp Penaeus monodon Exposed to Cadmium - Jian-An Xian; Bin Li; Hui Guo; Yu-Tao Miao; Jian-Min Ye; Li-Na Feng; Chao-Xia Ye; Xun-Bin Pan; An-Li Wang; Xuan-Ming Hao (Bulletin of Environmental Contamination and Toxicology, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

Systematic review of laparoscopy-assisted versus open gastrectomy for advanced gastric cancer - Long-yun Ye; Da-ren Liu; Chao Li; Xiao-wen Li; Ling-na Huang; Sheng Ye; Yi-xiong Zheng; Li Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Synthesis, structure, and biological assay of cinnamic amides as potential EGFR kinase inhibitors - Mao Zhang; Xiang Lu; Hong-Jia Zhang; Na Li; Yu Xiao; Hai-Liang Zhu; Yong-Hao Ye (Medicinal Chemistry Research, 2013)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

Global transcriptional profiles of Mycobacterium tuberculosis treated with plumbagin - Haiqing Ye; Zengshan Liu; Aizhen Guo; Junchao Liang; Na Guo; Fanli Zeng; Liqiang Liu; Lei Li; Jing Jin; Xiuping Wu; Yang Li; Mingyuan Liu; et al. (World Journal of Microbiology and Biotechnology, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)